2022
DOI: 10.3390/polym14194074
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of P(3HB-co-3HHx) Copolymers by a Newly Engineered Strain of Cupriavidus necator PHB−4/pBBR_CnPro-phaCRp for Skin Tissue Engineering Application

Abstract: Polyhydroxyalkanoates (PHAs) are biodegradable polymers synthesized by certain bacteria and archaea with functions comparable to conventional plastics. Previously, our research group reported a newly PHA-producing bacterial strain, Rhodococcus pyridinivorans BSRT1-1, from the soil in Thailand. However, this strain’s PHA synthase (phaCRp) gene has not yet been characterized. Thus, this study aims to synthesize PHA using a newly engineered bacterial strain, Cupriavidus necator PHB−4/pBBR_CnPro-phaCRp, which harb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The 1 H NMR was performed to verify the presence of 3HHx monomer in the copolymer synthesized by the strain C. necator PHB − 4/pBBR_CnPro- phaC Rp . Figure 3 illustrates the 1 H NMR band of H4, corresponding to the C4 methylene groups, and the 1 H NMR band of H6, corresponding to the C6 methyl group, indicating the formation of the P(3HB- co -3HHx) copolymer 15 , 24 , 29 . The monomer fractions of the copolymer were calculated according to the 1 H spectrum intensity ratio of the methyl components 30 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 1 H NMR was performed to verify the presence of 3HHx monomer in the copolymer synthesized by the strain C. necator PHB − 4/pBBR_CnPro- phaC Rp . Figure 3 illustrates the 1 H NMR band of H4, corresponding to the C4 methylene groups, and the 1 H NMR band of H6, corresponding to the C6 methyl group, indicating the formation of the P(3HB- co -3HHx) copolymer 15 , 24 , 29 . The monomer fractions of the copolymer were calculated according to the 1 H spectrum intensity ratio of the methyl components 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Han et al reported that the wild-type strains, Aeromonas spp., can produce P(3HB- co -3HHx) from vegetable oils and fatty acids via PHA synthase, which has a uniquely broad substrate specificity to (R)-3-hydroxyacyl-CoAs of C4-C6 39 . In this study, the P(3HB- co -3HHx) copolymer was synthesized by C. necator PHB − 4/pBBR_CnPro- phaC Rp 23 , 24 , a newly engineered bacterial strain, and the P(3HB- co -3HHx) production was improved using RSM. The results showed that the highest 3.6 ± 0.4 g/L of P(3HB- co -4 mol% 3HHx) was obtained using the RSM-optimized conditions in the flask scale.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations